2019
DOI: 10.1097/coc.0000000000000509
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Radiosurgery and Immune Checkpoint Inhibition

Abstract: Objectives: The anti-CTLA-4 and antiprogrammed cell death-1 (PD-1) therapies have significantly improved survival of patients with metastatic melanoma. However, there is limited data regarding the interaction between immunotherapy (IT) and stereotactic radiosurgery (SRS) in patients with brain metastasis, particularly how combination therapy may affect toxicity and intracranial tumor control. Methods: We retrospectively reviewed 26 patients with metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…The efficacy of radiosurgery with ICI remains unclear. Several reports have revealed that brain metastasis from melanoma and NSCLC has a favorable survival outcome when treated with ICI and SRS 8,30,31,40,43,[46][47][48] ; however, some studies have https://doi.org/10.3340/jkns.2020.0135…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of radiosurgery with ICI remains unclear. Several reports have revealed that brain metastasis from melanoma and NSCLC has a favorable survival outcome when treated with ICI and SRS 8,30,31,40,43,[46][47][48] ; however, some studies have https://doi.org/10.3340/jkns.2020.0135…”
Section: Discussionmentioning
confidence: 99%
“…Two studies [32,43] reported no grade 4 or 5 toxicities. Following the encouraging safety outcome from their previous study, Anderson et al [32] conducted a later study involving 21 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a dose-escalation study is warranted to maximize clinical efficacy with acceptable toxicities for prospective clinical trials. Encouraging results from preclinical and clinical studies support the synergistic effect of SBRT and ICI therapy against brain metastases from melanoma [68, 69]. Marrow-derived suppressor cells (MDSC) and immunosuppressive B cells could impede the antitumor activity induced by SBRT and immune therapy [70, 71].…”
Section: Discussionmentioning
confidence: 99%